The CIPP Model: Evaluation of the Football School Curriculum in Indonesia - Eka Nugraha; Een Sumarni (Universitas Pendidikan Indonesia, 2022)
The higher the number of football schools, the more diverse the quality of the schools. Evaluating the football school curriculum as an effort to determine the quality of the schools. The research design of this study used the Context, Input, Process, Product model (CIPP). It has used a descriptive quantitative method. The samples were two football schools, namely POR UNI football school, and Sidolig football school, selected through the purposive sampling technique. The research instruments were questionnaires and interviews given to 160 respondents, including principals, trainers, students, and parents. Data analysis was carried out quantitatively using t-scores and compared to the Glickmann quadrant. Based on the evaluation dan data analysis, the curriculum of POR UNI football school for the 13-17 years age group showed effective results, while the curriculum of Sidolig football school for the 13-17 years age group was less effective.